2008
DOI: 10.1590/s1677-04202008000200007
|View full text |Cite
|
Sign up to set email alerts
|

28-Homobrassinolide alleviates oxidative stress in salt-treated maize (Zea mays L.) plants

Abstract: The present investigation was undertaken to study the effects of 28-homobrassinolide on the activities of antioxidative enzymes such as superoxide dismutase (EC 1.15.1.1), guaiacol peroxidase (EC 1.11.1.7), catalase (EC 1.11.1.6), glutathione reductase (EC 1.6.4.2) and ascorbate peroxidase (EC 1.11.1.11), as well as protein and malondialdehyde concentrations in 30-d-old plants of Zea mays L. grown under salt stress. The seeds were soaked in 28-homobrassinolide solutions (0, 10 -8 , 10-6 and 10 -4 mM) for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 16 publications
4
20
0
Order By: Relevance
“…Our results of increasing concentration of POD activity corroborates with the findings of Arora et al (2008) who reported that increase in NaCl concentration increases the POD activity in maize plants. Chen et al (2007) also observed increase in POD activity in Vigna unguiculata subjected to salinity stress.…”
Section: P Ahmadsupporting
confidence: 92%
“…Our results of increasing concentration of POD activity corroborates with the findings of Arora et al (2008) who reported that increase in NaCl concentration increases the POD activity in maize plants. Chen et al (2007) also observed increase in POD activity in Vigna unguiculata subjected to salinity stress.…”
Section: P Ahmadsupporting
confidence: 92%
“…Excessive production of free radicals can lead to membrane disfunctioning. Higher POD activity in salt stressed plants corroborate with the results of Arora et al, (2008) and Ahmad (2010). Chen et al, (2007) demonstrated increased activity of POD in salt exposed Vigna unguiculata seedlings.…”
Section: Membrane Stability Index and Malonaldehyde (Mda)supporting
confidence: 85%
“…Lipid peroxidation rate was found to increase with increase of salt stress especially in sensitive cultivars [10] in this connection, Joshi et al [11] stated that with increasing level of salinity stress, the malondialdehyde (MDA) content increased in four Brassica juncea varieties. The accumulation of glycerol is an adaptive response of plants and other organisms to the lack of water and salinity stress.…”
Section: Introductionmentioning
confidence: 92%